Conservation and sustainable use of tropical fruit species diversity: Bioversity's efforts in Asia, the Pacific and Oceania - Bhag Mal; Rao, R.; Sthapit, B.R.; Sajise, P. (2011)
Asia, the Pacific and Oceania region is very rich in genetic diversity of tropical fruits. Although, fruits have always been important agricultural species, it is only in recent years that there is an increasing awareness of the potential of native tropical fruit species as good sources of dietary vitamins, minerals and energy. They also play a very signifi cant role for the wellbeing of the people through enhancing household income, employment generation particularly for women, and environmental protection. At the same time, their genetic diversity and even the species diversity is threatened due to various human interventions and concerted efforts are required to take corrective measures. Bioversity International, in collaboration with national partners, implemented in recent past several programmes for effective conservation and sustainable use of genetic resources of tropical fruits in the region and is continuing to do so. This paper describes the results of studies on various aspects of tropical fruit genetic diversity and species diversity as well as their sustainable use in major fruit growing countries in Asia, the Pacifi c and Oceania in the last decade and half. The studies included exploration and collecting, characterization and evaluation, identifi cation of promising/elite lines, documentation, conservation, training and capacity building, socio-economic analysis, information dissemination, collaboration and networking, impacts and sustainability of efforts. The paper also touches on the current efforts and future thrusts for tropical fruit species genetic resources conservation, management and sustainable use.